AWARENESS AND PRACTICE OF THROMBOPROPHYLAXIS AMONG SURGEONS IN TERTIARY CARE HOSPITALS OF KHYBER PUKHTUNKHWA - Khan, Zahir; Iqbal, Malik Javed; Wazir, Suraya; Khan, Mumtaz (Journal of Postgraduate Medical Institute, 2012)
Objective: To find out the awareness and practice of thromboprophylaxis among surgeons working in teaching hospitals of Khyber Pakhtunkhwa. Methodology: This was a descriptive study carried out in Hayatabad Medical Complex, Khyber Teaching Hospital, Lady Reading Hospital Peshawar and Ayub Teaching Hospital Abbottabad. Consultants from General and Orthopaedic surgery in four teaching hospitals working as senior registrar or above grades were included in the study and were interviewed using proforma about use of thromboprophylaxis. The results were analysed using SPSS version 10.0. Results: A total of 48 consultants participated in this study. 20 of these were orthopaedic surgeons and 28 were general surgeons. Thirty two (66.6%) of the consultants were using thromboprophylaxis but out of these, only 7 (22%) were following the national guide lines. Out of the 16 (33.4%) who were not using thromboprophylaxis, 10 (62.5%) consultants had the impression that it is not necessary while 4 (25%) thought that it increased the risk of bleeding and 2 (12.5%) consultants had the impression that it is expensive. Eight (16.7%) consultants said that they have departmental policy for thromboprophylaxis. Conclusion: Although majority of surgeons were using throboprophylaxis, however few were well versed about the guidelines and very few were following these.